The impact of pituitary adenomas on cognitive performance: a systematic review - Young, Ting-Chia; Lin, Kai-Yen; Li, Wan-Cheng; Huang, Chi-Ning; Tsai, Wen-Hsuan (Frontiers in Endocrinology, 2025)
PurposeIncreasing evidence suggests that beyond classical endocrine and visual symptoms, patients with pituitary adenoma (PA) may experience neurocognitive impairment, potentially resulting in reduced productivity and diminished quality of life. Prior studies have used diverse cognitive assessment tools across heterogeneous populations, leading to inconsistent findings. To address the variability, our study systematically analyzes the assessment batteries used in previous research, clarifying their corresponding cognitive domains. We seek to provide a more consistent and comprehensive understanding of the neurocognitive implications associated with PAs.MethodsThis study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses reporting guideline. Individual patient-level data, including clinical characteristics, tumor subtype, treatment interventions, hormonal status, and psychological outcomes, were systematically collected. Cognitive assessment tools were categorized according to their corresponding cognitive domains to facilitate domain-specific analyses.ResultsThis systematic review included 70 studies encompassing a total of 3,842 patients with PA. Of these, 60 studies employed either objective neuropsychological tests or subjective questionnaires to evaluate cognitive function. The most frequently utilized assessment was the Digit Span test, with 42.9% of studies reporting significant impairments in complex attention and executive functioning among patients with PA. Twelve studies focused on structural brain changes as assessed by magnetic resonance imaging, with half documenting volumetric reductions in gray matter. Across the various PA subtypes, a consistent decline in discrete cognitive domains was observed, most notably in memory and executive function. Treatment-related data were provided in 59 studies. Perioperative changes in cognitive performance were described in 14 studies, of which 11 reported post-surgical improvement in at least one cognitive domain. Twenty studies investigated the potential adverse effects of radiotherapy on cognitive function; among them, 16 found no significant differences following treatment. Eight studies examined the association between tumor size and cognitive impairment; seven reported no statistically significant correlation. In contrast, 24 studies identified a significant relationship between hormonal dysregulation and cognitive decline.ConclusionsThe literature contains heterogeneous findings about the cognitive performance, nature of cognitive impairment, and subsequent effects of treatment. Patients with PA may experience cognitive decline in specific areas and are notably affected by hormone levels, while treatment may lead to cognitive recovery. The proposed tiered cognitive evaluation approach can improve assessment consistency in future practice.